The Local Influence of Pioneer Investigators on Technology Adoption: Evidence from New Cancer Drugs - Agha, Leila; Molitor, David (The Review of Economics and Statistics, 2018)
Local opinion leaders may play a key role in easing information frictions associated with technology adoption. This paper analyzes the influence of physician investigators who lead clinical trials for new cancer drugs. By comparing diffusion patterns across 21 new cancer drugs, we separate correlated regional demand for new technology from information spillovers. Patients in the lead investigator's region are initially 36% more likely to receive the new drug, but utilization converges within four years. We also find that superstar physician authors, measured by trial role or citation history, have broader influence than less prominent authors.